Nerses the Graceful (short (biographica loverview and excerpt from the “General Epistle”) - Kortmosyan, Varand (Hakob) (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Հաղորդման մէջ համառօտ ներկայացուել են Սբ. Ներսէս Շնորհալու (Ներսէս Դ. Կլայեցի հայրապետ, Երգեցօղ) կենսագրական գիծերը, ինչպէս նաեւ Հայրապետի Թուղթ Ընդհանրականից՝ իշխանաւորներին ուղղուած գրութիւնը թարգմանուել է արաբերէնի: В статье в кратце представлена биография св. Нерсеса Шнорали (Клаэци, Сладкопевец), а так же отрывок из его «Соборного послания» в переводе на арабский язык. The article briefly presents the biography of St. Nerses the Graceful (Nerses of Kla, the Sweet Singer) as well as an excerpt from his “General Epistle” translated into Arabic.
Keywords: Religious studies